IDENTIFICATION OF CHALLENGES AND OPPORTUNITIES IN REALIZING GENDER EQUALITY IN SOCIETY - Hanifa, Nazwa Ihza; Saragih, Tini Rezeki; Putri, Yuana Wangsa; Syaharani, Latifah; Asti, Rahma Dwi; Putra, Ajib Atha Syah (Journal of Gender and Social Inclusion in Muslim Societies, 2025)
Gender equality is a key issue in efforts to achieve sustainable and inclusive development throughout the world. This article discusses the challenges and opportunities in achieving gender equality in society. The main challenges faced are gaps in access to education, employment and political decisions, as well as gender stereotypes that are deeply rooted in culture and social structures. But amidst these challenges, there is a huge opportunity for positive change. These opportunities include increasing public awareness and support for gender equality, expanding advocacy and support efforts, and developing technology that enables broader access and participation for women. By leveraging dynamic cross-sector collaboration and joint efforts between governments, non-governmental organizations, the private sector and civil society, we can bring about meaningful change towards improving gender equality. By analyzing these challenges and opportunities, this article provides insight into strategic steps that can be taken to achieve sustainable and inclusive gender equality in society.